2006
DOI: 10.1093/qjmed/hcl117
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal haemoglobin levels in acute coronary syndromes

Abstract: Abnormal haemoglobin levels were common in our ACS admissions. Anaemia was generally mild. Increasing age and interventional management were associated with anaemia, which in turn was associated with adverse in-hospital outcomes. Interventions to prevent and detect anaemia in this setting merit prospective testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
2
16
0
5
Order By: Relevance
“…Anemia was present in 28% of the ACS patients studied confirming that anemia is frequently found in patients with ACS, although the prevalence varies widely between 10% to 30% depending on the definition used in various studies. [1][2][3][4][5][6][7][8][9] In accordance with the findings linking anemia and poor clinical outcomes in ACS patients, this study demonstrated that ACS patients with anemia were more likely to be older, female, and associated with comorbidities like diabetes, hypertension, chronic renal failure, and stroke; [1][2][3][4][5][6][7][8][9]18,19 thus identifying a high-risk population with poor hematopoetic reserve. They were more likely to present with lower systolic blood pressure, higher heart rates, and higher Killip class and GRACE risk scores.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Anemia was present in 28% of the ACS patients studied confirming that anemia is frequently found in patients with ACS, although the prevalence varies widely between 10% to 30% depending on the definition used in various studies. [1][2][3][4][5][6][7][8][9] In accordance with the findings linking anemia and poor clinical outcomes in ACS patients, this study demonstrated that ACS patients with anemia were more likely to be older, female, and associated with comorbidities like diabetes, hypertension, chronic renal failure, and stroke; [1][2][3][4][5][6][7][8][9]18,19 thus identifying a high-risk population with poor hematopoetic reserve. They were more likely to present with lower systolic blood pressure, higher heart rates, and higher Killip class and GRACE risk scores.…”
Section: Discussionsupporting
confidence: 76%
“…One of the main findings of the present study is that admission anemia during ACS was not only related to statistically significant higher in-hospital mortality, 2,8,18 but also predicted 1-month 1,3,11,18 and 1-year mortality. [5][6][7]9,[23][24][25][26] The multiple regression models showed that this relationship persisted even after adjustment with GRACE risk score.…”
Section: Mortalitysupporting
confidence: 49%
See 2 more Smart Citations
“…For example, malnutrition and inflammation can cause hypoalbuminemia and also suppress erythropoeisis (24). Furthermore, the relationship of albumin to hemoglobin is not limited to dialysis patients; albumin concentration is strongly associated with anemia in patients admitted to the hospital with acute coronary syndromes (25). Finally, drugs that reduce inflammation, such as statins, are associated with reduced epo requirements (26).…”
Section: Discussionmentioning
confidence: 99%